Clinical effectiveness of a staff training intervention in mental health inpatient rehabilitation units designed to increase patients' engagement in activities (the Rehabilitation Effectiveness for Activities for Life [REAL] study): single-blind, cluster-randomised controlled trial. (January 2015) - Killaspy, Helen; Marston, Louise; Green, Nicholas; Harrison, Isobel; Lean, Melanie; Cook, Sarah; Mundy, Tim; Craig, Thomas; Holloway, Frank; Leavey, Gerard; Koeser, Leonardo; McCrone, Paul; et al.
Summary Background Mental health inpatient rehabilitation services focus on people with complex psychosis who have, for example, treatment-refractory symptoms, cognitive impairment, and severe negative symptoms, which impair functioning and require lengthy admission. Engagement in activities could lead to improvement in negative symptoms and function, but few trials have been done. We aimed to investigate the effectiveness of a staff training intervention to increase patients' engagement in activities. Methods We did a single-blind, two-arm, cluster-randomised controlled trial in 40 mental health inpatient rehabilitation units across England. Units were randomly allocated to either a manual-based staff training programme delivered by a small intervention team (intervention group, n=20) or standard care (control group, n=20). The primary outcome was patients' engagement in activities 12 months after randomisation, measured with the time use diary. With this measure, both the degree of engagement in an activity and its complexity are recorded four times a day for a week, rated on a scale of 0–4 for every period (maximum score of 112). Analysis was by intention-to-treat. Random-effects models were used to compare outcomes between study groups. Cost-effectiveness was assessed by combining service costs with the primary outcome. This study is registered with Current Controlled Trials (ISRCTN25898179). Findings Patients' engagement in activities did not differ between study groups (coefficient 1·44, 95% CI −1·35 to 4·24). An extra £101 was needed to achieve a 1% increase in patients' engagement in activities with the study intervention. Interpretation Our training intervention did not increase patients' engagement in activities after 12 months of follow-up. This failure could be attributable to inadequate implementation of the intervention, a high turnover of patients in the intervention units, competing priorities on staff time, high levels of patients' morbidity, and ceiling effects because of the high quality of standard care delivered. Further studies are needed to identify interventions that can improve outcomes for people with severe and complex psychosis. Funding National Institute for Health Research.